2017
DOI: 10.1101/165233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal Role of Beta Oscillations in Time Estimation

Abstract: The neural mechanisms underlying time perception are of vital importance to a comprehensive understanding of behavior and cognition. Recent work has pointed to a supramodal role for beta oscillations in coordinating endogenous timing mechanisms for the purpose of measuring temporal intervals. However, the majority of this work has employed paradigms relying on timed motor responses, which are confounded by beta’s established role in motor movement. Further, no study to date has tested if the alteration of beta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…During motor timing , an increase in β power indexes the length of produced time intervals. This pattern has also been reported during perceptual timing (Kulashekhar et al, 2016) and shown to be causally related to time estimation (Wiener et al, 2017). β oscillations have also been suggested to control temporal predictions (Arnal et al, 2014;Fujioka et al, 2012;Teki & Kononowicz, 2016;Iversen et al, 2009).…”
Section: α--β Pac Maintains the Precision Of Temporal Representationsmentioning
confidence: 55%
“…During motor timing , an increase in β power indexes the length of produced time intervals. This pattern has also been reported during perceptual timing (Kulashekhar et al, 2016) and shown to be causally related to time estimation (Wiener et al, 2017). β oscillations have also been suggested to control temporal predictions (Arnal et al, 2014;Fujioka et al, 2012;Teki & Kononowicz, 2016;Iversen et al, 2009).…”
Section: α--β Pac Maintains the Precision Of Temporal Representationsmentioning
confidence: 55%